PHYTOPLANKTON FORMATION UNDER CONDITIONS OF DIFFERENT TYPES OF POLLUTION AND CHANGES IN THE WATER QUALITY OF THE VOGHJI RIVER: (REPUBLIC OF ARMENIA) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
An assessment of the ecological state of the Voghji River and its catchment basin according to chemical and biological indicators in the period 2018–2019. New taxa were discovered in phytoplankton, when contaminated with heavy metals and organic substances. A decrease in community stability and an increase in the role of Сyanoprokaryotes and green algae in plankton were observed, which can be used for phytoremediation of the degraded ecosystem of the Voghji River.
Keywords: Сyanoprokaryota; heavy metals and organic substances; phytoremediation; Shannon index; environmental and economic conflict